Extracellular Vesicle Functionalized Melt Electrowritten Scaffolds for Bone Tissue Engineering. Issue 10 (28th July 2021) - Eichholz, Kian F.; Federici, Angelica; Riffault, Mathieu; Woods, Ian; Mahon, Olwyn R.; O'Driscoll, Lorraine; Hoey, David A.
Abstract : Mechanobiological cues arising directly via tissue/scaffold mechanics or indirectly via mechanically activated cell secretomes represent potent stimuli that mediate cell behavior and tissue adaptation. Exploiting these cues in regeneration strategies holds great promise for tissue repair. Herein, indirect biophysical cues originating from osteocytes in combination with direct biophysical cues from melt electrowritten (MEW) scaffolds to form a single engineered construct with the aim of synergistically enhancing osteogenesis are harnessed. The secretome of mechanically activated osteocytes is collected within conditioned media (CM) and extracellular vesicles (EVs) are subsequently isolated. Building on MEW microfibrous scaffolds with controlled microarchitecture and mineral nanotopography optimized for bone repair, a protocol is developed to functionalize these materials with CM or EVs. Human marrow stromal cell (MSC) proliferation is enhanced in both CM and EV functionalized scaffolds. EV functionalized scaffolds are further found to significantly enhance MSC osteogenesis, with enhanced alkaline phosphatase expression, collagen production, and mineralization compared with control scaffolds. Furthermore, enhanced formation of mineralized nodules is identified in EV functionalized materials. Combining direct biophysical cues provided by the fibrous architecture/mineral nanotopography with the indirect cues provided by EVs, these constructs hold great promise to enhance the repair of damaged bone in a physiologically relevant manner. Abstract : Melt electrowritten (MEW) scaffolds are functionalized with extracellular vesicles from mechanically stimulated osteocytes. This yields a hybrid scaffold with defined microfibrous architecture and binds potent biological cues, which results in enhanced human stem cell osteogenesis and mineralization. This seamless combination of biomimetic physical and biological cues holds great promise for the repair of damaged bone in a physiologically relevant manner.